PENDIDIKAN AKHLAK DALAM KELUARGA TERHADAP PERILAKU IHSAN SISWA - Abu Hanifah, Oking Setia Priyatna, Mulyadi Kosim (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2020)
The purpose of this study was to determine the extent of moral education in the family towards the ihsan behavior of students at MTs Al-Atiqiyah karadenan Cibinong. This research uses field research (field research) using a quantitative approach. To find a correlation between Variable X (Moral Education) and Variable Y (Ihsan Behavior). With the student population technique, the total number of grade IX students is 30 people. The data collection technique used a questionnaire given to 30 students at MTs Al-Atiqiyah Karadenan Cibinong. The techniques used for data collection were observation, documentation, and questionnaires (questionnaires). As well as the analysis technique used is statistical analysis with the percentage formula. This formula is used to analyze the answers to the questionnaire given to respondents. Furthermore, to analyze the effect of moral education in the family on the ihsan behavior of students at MTS Al-Atiqiyah Karadenan Cibinong, the writer used the product moment correlation formula. After the research was conducted, the authors obtained results with an average rate of 53.33% for family morality education at MTs Al-Atiqiyah Karadenan Cibinong and 49.3% for ihsan behavior at MTs Al-Atiqiyah} Karadenan Cibinong. While the results of the correlation test of moral education in the family on the ihsan behavior of students at MTs Al-atiqiyah Karadenan Cibinong were 0.070.